1952
DOI: 10.2136/sssaj1952.03615995001600030014x
|View full text |Cite
|
Sign up to set email alerts
|

Field and Laboratory Studies of Nitrite Accumulation in Soils

Abstract: A field and laboratory study of nitrite accumulation under arable soil conditions was carried out using a considerable number of nitrogen fertilizers applied at various seasons of the year. The results show that nitrite will accumulate under neutral or alkaline soil conditions provided the rate of fertilization is heavy enough to produce a considerable concentration of the ammonium ion. Under field conditions, especially where the soils are not warm enough for rapid biological activity, the nitrite produced ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

1965
1965
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Despite the importance of soil NO 2 -to atmospheric chemistry (Su et al, 2011;Oswald et al, 2013) NO 2 -is rarely detected in soils, limiting our ability to observe linkages between soil N-cycling processes and atmospheric chemistry. In spite of the fast reactivity of NO 2 -in soils, however, it accumulates under at least two conditions: (i) when high soil ammonium (NH 4 + ) concentrations and pH adversely affect the microbes consuming NO 2 - (Chapman and Liebig, 1952;Van Cleemput and Abdullahi, 1996), and (ii) in drying soils where solutes concentrate in hydrologically disconnected microsites (Davidson et al, 1991;Xie et al, 2001;Nejidat, 2005;Gelfand and Yakir, 2008;Parker and Schimel, 2011).…”
Section: N Itrite (No 2 -) Is An Important Intermediate In Nitrificatmentioning
confidence: 99%
“…Despite the importance of soil NO 2 -to atmospheric chemistry (Su et al, 2011;Oswald et al, 2013) NO 2 -is rarely detected in soils, limiting our ability to observe linkages between soil N-cycling processes and atmospheric chemistry. In spite of the fast reactivity of NO 2 -in soils, however, it accumulates under at least two conditions: (i) when high soil ammonium (NH 4 + ) concentrations and pH adversely affect the microbes consuming NO 2 - (Chapman and Liebig, 1952;Van Cleemput and Abdullahi, 1996), and (ii) in drying soils where solutes concentrate in hydrologically disconnected microsites (Davidson et al, 1991;Xie et al, 2001;Nejidat, 2005;Gelfand and Yakir, 2008;Parker and Schimel, 2011).…”
Section: N Itrite (No 2 -) Is An Important Intermediate In Nitrificatmentioning
confidence: 99%
“…The most probable explanation is that the expected microbial reduction of nitrite is beginning to build up. DISCUSSION Accumulation of nitrite has frequently been observed following the application of ammonium (Chapman & Liebig, 1952) or urea (Court, Stephen & Waid, 1964) to alkaline soils, resulting in ammonia toxicity towards Nitrobacter, and in waterlogged soils to which soluble carbon has been added to encourage dissimilatory nitrate reduction (true denitriflcation) (Bremner & Shaw, 1958;Greenwood, 1962). Cooper & Smith (1963) have suggested that in alkaline soils nitrite accumulates under waterlogging because its removal is the ratelimiting process for denitriflcation.…”
Section: -2mentioning
confidence: 99%
“…Van den Hende (1950) observe des dĂ©gĂąts (manques Ă  la levĂ©e, brulĂ»res de feuillage) sur certaines espĂšces cultivĂ©es, pour des doses de 100-160 kg d'azote.ha -1 et suggĂšre une utilisation des sels nitreux comme dĂ©sherbant. Si l'ion nitreux peut ĂȘtre directement assimilĂ© et utilisĂ© par la plante (Lemaire, 1969), il se rĂ©vĂšle souvent toxique (Paul et Polle, 1965;Oke, 1966) dĂšs que la concentration en azote nitreux atteint 50 mg.kg -1 de sol dans la rhizosphĂšre (Goyal et Huffaker, 1982) (Chapman et Liebig, 1952;Tyler et al, 1959). Ce ralentissement est attribuĂ© Ă  la prĂ©sence d'ammoniac libre qui exerce une action inhibitrice sur Nitrobacter, en milieu acide l'acide nitreux non dissociĂ© exercerait un effet semblable (Anthonisen et al, 1976).…”
Section: Introductionunclassified